High expression of CD10 in anaplastic thyroid carcinomas. Issue 3 (28th June 2018) - Nakazawa, Tadao; Kondo, Tetsuo; Vuong, Huy Gia; Odate, Toru; Kawai, Masataka; Tahara, Ippei; Kasai, Kazunari; Inoue, Tomohiro; Oishi, Naoki; Mochizuki, Kunio; Ito, Koichi; Katoh, Ryohei
Abstract : Aims: CD10 is an endopeptidase that degrades various bioactive peptides in the extracellular matrix. In addition to enzymatic degradation, it affects multiple intracellular signal transduction pathways. CD10 expression has been extensively studied in human epithelial cancers of numerous organs and sites. However, its presence in thyroid carcinomas, especially in anaplastic thyroid carcinoma (ATC), has not been fully determined. An actual CD10 expression in thyroid lesions including a large series of ATC was evaluated. Methods and results: We examined CD10 by immunohistochemistry (IHC) in 152 thyroid lesions: nine adenomatous goitres (AGs) and 143 tumours, including 47 anaplastic carcinomas. IHC showed diffuse and strong positivity for CD10 in the epithelial components of almost all ATCs. However, epithelia with squamous metaplasia and oncocytic change from AGs, follicular adenomas and differentiated carcinomas had focal CD10 reactivity. Some papillary thyroid carcinomas (PTCs), along with the PTC components of some ATCs, showed CD10 positivity in fibroblast‐like stromal cells and fibrous material. Conclusion: Our results imply that the CD10 expression pattern depended on the histotypes of thyroid lesions. When possible metastatic tumours and non‐epithelial tumours are excluded, high CD10 expression may be useful in determining whether a primary thyroid carcinoma includes an anaplastic component.